1999
DOI: 10.1109/61.736710
|View full text |Cite
|
Sign up to set email alerts
|

Circuit-breaker requirements for alternative configurations of a 500 kV transmission system

Abstract: This paper describes the study made to assess the electrical stresses imposed on line circuit breakers of a new SOOkV, AC expansion of the FURNAS transmission system, to be possibly installed in the Brazilian central region. The study has considered three configurations of the transmission lines, two of which assuming the use of compact towers. In one of these two cases the lines would have high surge-impedance loading. Digital simulations have been made with the aid of the Alternative Transients Program (ATP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…In order to avoid the pre-arcing effects, it was considered that the dv CB /dt is greater than the maximum value of the power system voltage derivative [15].…”
Section: Proposed Methods Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid the pre-arcing effects, it was considered that the dv CB /dt is greater than the maximum value of the power system voltage derivative [15].…”
Section: Proposed Methods Evaluationmentioning
confidence: 99%
“…Concerning the surge arresters, two situations were analyzed: 396 kV and 420 kV class arresters. The 396 kV arrester has a protection level of 783 kV at 2 kA and the 420 kV arrester, which is normally used at the 500 kV Brazilian Power System [15], has a protection level of 830 kV at 2 kA.…”
Section: Proposed Methods Evaluationmentioning
confidence: 99%
“…Investigation of resonant overvoltage in SHVTL. The main direction of previous studies of overvoltage [2][3][4][5][6][7][8][9] using mathematical modeling was focused on the development and application of mathematical models for quantitative results in order to limit overvoltage at the main frequency. They did not consider the physical processes of the development of resonance overvoltage on even harmonic components, although the occurrence of this type of overvoltage is known for a relatively long time.…”
mentioning
confidence: 99%
“…It is shown that the necessary condition for the occurrence of overvoltage is the coincidence of two factors: the length of the SHVTL and the angle of switching of the poles of the circuit breaker. It should be noted that the length of the SHVTL is one of the determining factors for overvoltage not only in non-sinusoidal, but also in asymmetrical modes [6][7][8][9], although the source of distortion of the mode, and the appearance of the corresponding resonant circuits in these cases are different. But the length of the line is determined when designing the track of the line, and the factor of the possibility of occurrence of overvoltage is not taken into account.…”
mentioning
confidence: 99%
See 1 more Smart Citation